Prevalence of supernumerary teeth in peruvian children and adolescents treated at a university clinic - Gálvez Cubas, Meliza Lizbeth (2021)
Objective: Determine supernumerary teeth prevalence using digital panoramic radiographs in patients pediatric and adolescent treated at Dental Center of Cayetano Heredia Peruvian University between 2015- 2018 years. Materials and methods: The present study is descriptive, observational, retrospective and cross-sectional. Panoramic radiographs evaluation of Oral and Maxillofacial Radiology Service database from Dental Teaching Center of Cayetano Heredia Peruvian University was carried out, between 3 to 17 years, where supernumerary teeth (ST) presence was evaluated to find prevalence. Results: A total of 3,189 panoramic radiographs, 6.71% prevalence of DS was obtained. By gender, it was higher in men with 68.22%. The most frequent location was in anterosuperior sector (75.52%), rudimentary form (conical-tubercular) was 66.9%. As for the orientation, vertical position was the most frequent with 72.14%. Finally, intraosseous level was 59.31%. Conclusions: The prevalence of DS through panoramic radiographs in pediatric and adolescent patients treated at the teaching dental center of Cayetano Heredia Peruvian University was 6.71%.